Strategi Motivasi Kerja Pegawai Di Kantor Kelurahan Bira Kecamatan Tamalanrea Kota Makassar - Febrianti, Riska; Rahim, Samsir; Wahid, Nur (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to determine the Implementation of Employee Work Motivation Strategy at the Bira Village Office, Tamalanrea District, Makassar City. This studyused  a qualitative research method with a descriptive type of research. Data collection techniques used interviews, observation, and documentation. The results of the study show 5 indicators of implementing employee motivation strategies at the Bira Village Office, such as 1) Involving, that the leadership involved employees before making decisions and involving them to attend community events hadrun well. 2) Communication, that the leadership had a good communicationso that have a good relationship between the employees and the leadership of Bira Village. 3) Recognition, that the leadership provided rewards that were in accordance with the performance of their employees such as providing small gifts, certificates, and also giving direct congratulations. 4) Delegated authority, that the leadership enforces this delegation of authority to give responsibility and trust to its employees so that they did not an obligation. 5) Reciprocal Attention, that the Leader gave permission and fulfilled the facilities in accordance with the work of his employees so that they could carry out their work as expected.Keywords: Strategi, Work Motivation.